p63 Expression in Ductal Carcinoma In Situ (DCIS) of the Breast and Its Correlation with Histopathological Grading and Morphological Variants - Runky Pebranka; Aswiyanti Asri; Tofrizal (HM Publisher, 2025)
Background: Ductal carcinoma in situ (DCIS) is a non-invasive breast cancer with varying potential for progression to invasive carcinoma. Myoepithelial cells (MECs) play a role in preventing this progression, and their absence is a hallmark of invasive disease. The p63 protein is a myoepithelial marker that can be assessed by immunohistochemistry (IHC). This study aimed to evaluate the relationship between p63 expression in MECs, the grade of DCIS, and the morphological subtype of DCIS. Methods: A cross-sectional study was conducted on 35 cases of DCIS diagnosed at the Anatomical Pathology Laboratory of Dr. M. Djamil General Hospital Padang. Paraffin blocks were collected, and Hematoxylin and Eosin (H&E) slides were reviewed to confirm the diagnosis and determine the histopathological grading (low, intermediate, and high) and morphological variants (comedo and non-comedo) of DCIS. Paraffin blocks were re-cut for p63 immunohistochemical staining. The extent of p63 expression was classified as complete or incomplete. Results: The majority of DCIS cases were high grade (54.3%) and of the non-comedo subtype (68.4%). All cases with complete p63 expression were of low histologic grade, while all cases with incomplete p63 expression were of high histologic grade. The results of the Chi-square test showed a statistically significant relationship between p63 expression and histopathological grading (p<0.001). There was no statistically significant relationship between p63 expression and morphological variant. Conclusion: The absence of p63 expression in DCIS is associated with high histologic grade. This finding suggests that p63 IHC may be a useful adjunct in evaluating DCIS.